Analyzing Dictation Errors in Arabic Writing: Identifying Causes and Strategies for Improvement among Senior High School, Medan - Nasution, Zakiah Mardiah; Al Rasyid, Harun (STUDI ARAB, 2025)
This study is based on the studentsâ€™ low ability to write Arabic vocabulary correctly, particularly in the aspect of imlÄâ€™.Many tenth-grade students at MAS YASPI Labuhan Deli Medan still make basic writing errors in letters, harakat, and word forms, indicating a gap between expected vocabulary mastery and actual performance. The main objective of this study is to analyze the types of imlaâ€™ errors made by students, identify the causes, and formulate appropriate teaching strategies to reduce these errors. This research employed a qualitative descriptive method with a case study design. The subjects consisted of 20 tenth-grade students. Data were collected through written tests, interviews, and documentation, and analyzed using identification, classification, interpretation, and error analysis techniques. The findings reveal eight categories of imlÄâ€™â€™ errors, with the most common being letter substitution and the omission or addition of letters. Contributing factors include limited understanding of imlaâ€™ rules, lack of writing practice, and less supportive teaching methods. The study recommends strategies such as applying imlÄâ€™ istimÄâ€˜Ä« and imlÄâ€™ manáº“Å«r methods, along with strengthening studentsâ€™ understanding of writing rules and focused writing practice, as contributions to improve Arabic writing instruction.